2008
DOI: 10.1002/elan.200804264
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Mercapto‐Compound‐Gold‐Nanoparticle‐Modified Carbon Paste Electrode for Potentiometric Determination of Cadmium(II)

Abstract: A new modified carbon paste electrode (CPE) based on a recently synthesized ligand [2-mercapto-5-(3-nitrophenyl)-1,3,4-thiadiazole] (MNT), self-assembled to gold nanoparticles (GNP) as suitable carrier for Cd(II) ion with potentiometric method are described. The proposed electrode exhibits a Nernstian slope of 29.4 AE 1.0 mV per decade for Cd(II) ion over a wide concentration range from 3.1 Â 10 À8 to 3.1 Â 10 À4 mol L À1 . The detection limit of electrode was 2.0 Â 10 À8 mol L À1 of cadmium ion. The potentiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…GNPs are commonly used for fabrication of modified carbon paste electrode in voltammetric and amperometric methods, but we applied GNP-carbon paste electrode for potentiometric method for the first time. In our previous work, we demonstrated that the carbon paste electrodes modified with sulfur-containing compounds self-assembled on gold nanoparticles constitute the excellent sensors for potentiometric determination of copper and cadmium cations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…GNPs are commonly used for fabrication of modified carbon paste electrode in voltammetric and amperometric methods, but we applied GNP-carbon paste electrode for potentiometric method for the first time. In our previous work, we demonstrated that the carbon paste electrodes modified with sulfur-containing compounds self-assembled on gold nanoparticles constitute the excellent sensors for potentiometric determination of copper and cadmium cations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles in CPEs have been exploited for the detection of metal ions. 744,745 Other nanoparticles with electrocatalytic properties are metal oxides, some of them being used for environmental sensing (i.e., SiO 2 746 or ZrO 2 747) . Note that the particular case of nanosized materials will be treated in the next chapter.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…GNPs are commonly used for fabrication of modified carbon paste electrode in voltammetric and amperometric methods, but we applied GNP-carbon paste electrode for potentiometric method. In our previous works, we demonstrated that the carbon paste electrodes modified with sulfur-containing compounds self-assembled on gold nano-particles constitute the excellent sensors for potentiometric determination of some metal cations [25][26][27]. The sol-gel route provides a useful method to prepare inorganic and organic-inorganic hybrid materials for use in chemical analysis.…”
Section: Introductionmentioning
confidence: 99%